Does nutritional status influence early child development? Evidance from infants in Bantul, Yogyakarta, Indonesia - Putri, Adelia Kholila; Ayuningrum, Lia Dian; Aryani, Farida; Arifin, Siti Roshaidai Mohd (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2025)
ABSTRAKLatar Belakang: Perkembangan anak usia 1-24 bulan sangat dipengaruhi oleh status gizi. Kekurangan gizi dapat menghambat pertumbuhan fisik, kognitif, serta meningkatkan risiko stunting. Data WHO pada tahun 2024 mencatat 23,2% anak di bawah 5 tahun mengalami stunting. Sementara itu, laporan Survei Status Gizi Indonesia menunjukkan prevalensi 19,8% pada tahun 2024. Dinas Kesehatan Bantul mencatat 7,01% balita mengalami stunting pada Juni 2024, Puskesmas Srandakan tercatat prevalensi tertinggi yaitu 13,94%.Tujuan: Mengetahui hubungan status gizi terhadap perkembangan anak usia 1-24 bulan.Metode: Penelitian survei analitik dengan desain cross-sectional ini dilakukan di posyandu wilayah kerja Puskesmas Srandakan pada 14 Mei–11 Juni 2025. Sebanyak 104 anak usia 1–24 bulan dipilih melalui cluster random sampling. Status gizi diukur dengan antropometri dan perkembangan anak menggunakan KPSP. Analisis data menggunakan uji korelasi Spearman Rank.Hasil: Mayoritas anak memiliki status gizi baik (83,7%) dan perkembangan yang sesuai (68,3%). Analisis statistik menggunakan uji Spearman Rank menunjukkan tidak terdapat hubungan yang signifikan antara status gizi dan perkembangan anak dengan nilai p = 0,976.Kesimpulan: Penelitian ini menunjukkan tidak terdapat hubungan signifikan antara status gizi dan perkembangan anak usia 1–24 bulan di wilayah kerja Puskesmas Srandakan, Bantul. Meskipun sebagian besar anak bergizi normal, variasi perkembangan tetap ditemukan pada semua kelompok gizi. Temuan ini mengindikasikan bahwa faktor lain—seperti stimulasi, praktik pengasuhan, dan lingkungan psikososial—juga berperan penting. Oleh karena itu, peningkatan perkembangan anak perlu mengintegrasikan intervensi gizi dengan edukasi pengasuhan dan stimulasi yang lebih terarah. KATA KUNCI: baduta; perkembangan anak; status gizi; stunting                                                                                                                                                                                    ABSTRACTBackground: The development of children aged 1-24 months is significantly influenced by nutritional status. Malnutrition can inhibit physical and cognitive growth, and increase the risk of stunting. WHO data in 2024 recorded 23.2% of children under 5 years old experiencing stunting. Meanwhile, the Indonesian Nutritional Status Survey report showed a prevalence of 19.8% in 2024. The Bantul Health Office recorded 7.01% of toddlers experiencing stunting in June 2024, while the Srandakan Community Health Center recorded the highest prevalence at 13.94%.Objective: To determine the relationship between nutritional status and the development of children aged 1-24 months.Method: This analytical survey with a cross-sectional design was conducted at the integrated health service post (posyandu) in the working area of the Srandakan Community Health Center. Total of 104 children aged 1-24 months were selected through cluster random sampling. Nutritional status was measured using anthropometry and child development using the KPSP. Data analysis used the Spearman Rank correlation test.Results: The majority of children had good nutritional status (83.7%) and appropriate development (68.3%). Statistical analysis using the Spearman Rank test showed no significant relationship between nutritional status and child development with a p-value of 0.976.Conclusion: This study shows no significant relationship between nutritional status and development in children aged 1–24 months in the Srandakan Community Health Center (Puskesmas) area, Bantul. Although most children had normal nutrition, developmental variations were found across all nutrition groups. These findings indicate that other factors—such as stimulation, parenting practices, and the psychosocial environment—also play a significant role. Therefore, improving child development requires integrating nutritional interventions with more targeted parenting education and stimulation. KEYWORD: child development; infant; nutritional status; stunting  Article submitted on August 05, 2025; Articles revised on September 11, 2025; Articles received on November 20, 2025; Articles available online on November 28, 2025